PERAN PUSTAKAWAN DALAM MENINGKATKAN LITERASI DIGITAL PADA MAHASISWA DI UNIVERSITAS ISLAM NEGERI (UIN) RADEN MAS SAID SURAKARTA - Muhammad Sharon Bholawi; Fauzan Fahmi Hamid; Mega Alif Marintan (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
The development of information technology requires universities, including the State Islamic University (UIN) Raden Mas Said Surakarta, to improve digital literacy among students. Librarians play an important role in this process, not only as information managers, but also as educators, facilitators, and academic partners. This study aims to analyze the role of librarians in improving the digital literacy of students at UIN Raden Mas Said Surakarta. The method used is a descriptive qualitative approach with interview techniques with four librarians. The results of the study show that librarians actively provide mentoring services, information literacy training, and academic ethics education. However, challenges such as low student participation, limited digital collections, and minimal budget are obstacles to optimizing these roles. This study concludes the importance of collaborative strategies between librarians, lecturers, and campus parties to create a sustainable digital literacy ecosystem.